2006
DOI: 10.1093/brain/awl304
|View full text |Cite
|
Sign up to set email alerts
|

Assessing seizure dynamics by analysing the correlation structure of multichannel intracranial EEG

Abstract: Epileptic seizures are commonly characterized as 'hypersynchronous states'. This habit is doubly misleading, because seizures are not necessarily synchronous and are not unchanging 'states' but dynamic processes. Here the temporal evolution of the correlation structure in the course of 100 focal onset seizures of 60 patients recorded by intracranial multichannel EEG was assessed. To this end a multivariate method was applied that at its core consists of computing the eigenvalue spectrum of the zero-lag correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
304
3
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(341 citation statements)
references
References 34 publications
27
304
3
7
Order By: Relevance
“…for financial series [9][10][11][12][13][14][15][16][17][18][19][20], electroencephalographic (EEG) recordings [21,22], magnetoencephalographic (MEG) recordings [23] and a variety of other multivariate data. In this paper, we investigate the same approach to analysis SenseCam lifelog data streams.…”
Section: Introductionmentioning
confidence: 99%
“…for financial series [9][10][11][12][13][14][15][16][17][18][19][20], electroencephalographic (EEG) recordings [21,22], magnetoencephalographic (MEG) recordings [23] and a variety of other multivariate data. In this paper, we investigate the same approach to analysis SenseCam lifelog data streams.…”
Section: Introductionmentioning
confidence: 99%
“…Along different lines of evidence, moreover, eigenvector analysis has indicated that towards seizure end such an initial desynchronization is followed by a reconfiguring hypersynchronization phase, which may thus even play a beneficial role as a mechanism for seizure termination (Schindler et al, 2007). These findings constitute a departure from the traditional view, which considers seizures as events of temporally constant, global hypersynchrony (Schindler et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Along different lines of evidence, moreover, eigenvector analysis has indicated that towards seizure end such an initial desynchronization is followed by a reconfiguring hypersynchronization phase, which may thus even play a beneficial role as a mechanism for seizure termination (Schindler et al, 2007). These findings constitute a departure from the traditional view, which considers seizures as events of temporally constant, global hypersynchrony (Schindler et al, 2007). Also, our result regarding the epoch course of the Shannon entropy lends further support against the hypothesis of constant, global hypersynchrony during seizures, since synchronous processes are associated with low entropy which, in contrast, we found to be largest at ictal mid-time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations